Strategi Pendayagunaan dan Pengelolaan Wakaf Tunai di Indonesia - Atabik, Ahmad (ZISWAF, 2014)
This article describes the cash waqf management strategies inIndonesia. Begins with understanding endowment perspective of Islamiclaw and the juridical basis of the cash endowments. Further discussion aboutthe problems of the management of the funds cash waqf, covered in it aboutthe rigidity of Muslims against the waqf, understanding still mistakenlyamong some Muslims about cash waqf, and the lack of professionalism ofthe management of waqf (nadzir waqf) and managing waqf property eitherin the form of cash waqf or not cash. At the end of the discussion talkedabout cash waqf management strategies are covered in it on a nationalscale the importance of Waqf Institution in institutions of IndonesianWaqf Board Beran as a supervisor and management of waqf productively.Formation BWI has the objective to organize the management of the nationaladministration, manage their own waqf property entrusted to him, especiallywith regard to the productive waqf land. Discussed also about buildingcommunity self-reliance by implementing and managing both cash waqf.